Goarno, A Web-based Application to Assist Duolingo English Test Takers : An Analysis based on Teachers’ Perspectives - Rahayu, Setya Putri; Sri Rejeki (JELLT (Journal of English Language and Language Teaching), 2024)
Duolingo English Test (DET) has become quite popular recently. It has answered the challenge of language test which previously placed IELTS or TOEFL IBT as the most reliable forms of English test after the popularity of TOEFL ITP. Based on the components of the test, Duolingo includes speaking and writing as productive skills into it; however TOEFL ITP does not include those skills. The most significant tacit that makes Duolingo as the choice of English proficiency test is that within its complete tested skills covering speaking, writing, reading, and listening, DET offers a lower price than IELTS and TOEFL IBT. It prices only a third of those tests. With a relatively new form of test, the availability of practice test and materials related to DET is still limited. Goarno, a web-based application which contain complete simulation tests and feedbacks, can help DET takers to boost their English capability in taking a DET. The study aims to investigate the significance of Goarno to boost DET takers in increasing their targeted score (1); it also aims to examine teachers effort to support students in using Goarno as an autonomous learning media (2).